Tourism, Traditional Handicrafts, and Community Economic Development: A Value Chain Analysis of Phuoc Tich Heritage Village, Vietnam - Nguyen, Duong Giang (Auckland University of Technology, 2015)
The overall aim of this doctoral study is to explore the use of the value chain analysis (VCA) approach in understanding the economic linkages between tourism and community economic development in traditional handicraft villages in Vietnam, using the case of Phuoc Tich pottery village. The focus of the thesis is on the economic linkages between the tourism industry and a traditional handicraft village and how these translate into community economic development (CED). This focus enables me to highlight the strengths and weaknesses of VCA and to make some modifications to the approach. Community economic development through traditional handicraft tourism requires a deep understanding of three important aspects: the tourism industry, traditional handicraft sectors, and the community where these are connected together. The thesis uses the production chain as an analytic tool to understand the way in which different elements come together in pottery production, and the tourism value chain is then used to identify how the tourism-related stakeholders engage with the pottery production. Phuoc Tich Heritage village, situated in Thua Thien Hue province, is well known for its traditional pottery crafts and ancient houses. Phuoc Tich village is an emerging tourist destination and provides the case study used in this thesis to explore multiple stakeholders’ perspectives on tourism and traditional handicraft development. To achieve some degree of immersion, the researcher lived in the case study village for four months. The core data collection tools used were semi-structured interviews with tourists, local community members, government officials, travel agents and tour operators, local entrepreneurs, and experts from non-governmental organisations (NGOs). A written survey was also conducted with tourists. The interviews and questionnaire were supported by field observations and informal discussions with a number of stakeholders. The findings show that if a tourism-related traditional handicraft industry is to be successful in rural areas, it requires better collaboration between all associated stakeholders and a deeper understanding of tourists’ motivations and local residents’ needs. In addition, this research contributes the finding that tourists’ direct participation in traditional handicraft production chains can increase tourists’ perceptions of the authenticity of their experiences. This thesis makes an important contribution to the understanding of how tourism and traditional handicrafts can be combined and contribute to the economy of communities. The thesis identifies and describes the key elements of the current value chain for Phuoc Tich pottery production and of the tourism industry in Thua Thien Hue province. The characteristics and behaviours of the tourists who visit the Phuoc Tich tourism pottery chain are also described. The specific roles of other external stakeholders in the sustainable development of traditional handicraft in the tourism value chain are detailed. The findings show how direct participation in the handicraft (pottery) production chain can both enhance tourist satisfaction when they visit a traditional handicraft village and increase economic benefits for local residents. More specifically, the research builds on current theories around tourist behaviour, VCA and the participation of the local community in the sustainable development of tourist destinations, especially in less-developed countries. This study will be of assistance to future researchers gathering information in other settings where handicraft, tourism and CED are linked.
Keywords: Tourism; Handicraft village; Traditional handicrafts; Community economic development; Value chain analysis; Multiple stakeholders